Peninjauan Faktor Keamanan Penanganan Longsoran Ruas Jalan Batas Kota Maros – Batas Kabupaten Bone Dengan Metode Fellenius dan Plaxis - Herlambang, Andy; Lebang, Fauzy; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Avalanche handling on the bts road section. Maros City – bts. Kab. Bone needs to review the value of the safe factor of the handling method applied.  This study aims to quantitatively examine the influence of geotextiles and retaining walls on the magnitude of the value of the safe factor on a slope.  This analysis uses data from the results of avalanche handling work on KM.89+995-90+045 and KM.90+395-90+405. In this study, 2 methods were used, namely the Fellenius method and the Plaxis program method. The results of this study show that the amount of safe factor values from the handling methods used at KM.89+995-90+045 and KM.90+395-90+405 locations is 2.71 and 2.27 obtained from the results of data processing using the Plaxis program, while using the Fellenius method the safe factor values are 2.70 and 1.66. Thus each safe factor value obtained is greater than the established safe factor value ( Fs > 1.5).